Combined spinal-epidural anesthesia and non-pharmacological methods of pain relief during normal childbirth and maternal satisfaction: a randomized clinical trial - Orange,Flavia Augusta de (2012)
OBJECTIVE: The objective of this study was to compare maternal satisfaction with childbirth according to whether or not combined spinal-epidural anesthesia (CSE) of pain relief was used during labor. METHODS: A randomized, open clinical trial was performed with 70 pregnant women, 35 of whom received CSE anesthesia while 35 received only non-pharmacological forms of pain relief during labor. The variables evaluated were visual analogue scale (VAS) pain score, maternal satisfaction with the technique of pain relief used during childbirth and with delivery, the patient's intention to request the same technique in a subsequent delivery, and loss of control during delivery. RESULTS: VAS pain score decreased significantly in patients receiving CSE during vaginal delivery. Furthermore, maternal satisfaction with the technique of pain relief and with delivery was higher in the CSE group, and around 97% of the patients would repeat the same technique at future deliveries compared to 82.4% of the women in the group using only non-pharmacological methods. With respect to the women's impressions of their control during delivery, approximately half the women in both groups felt that they had lost control at some point during the process. CONCLUSION: The use of CSE was associated with a significant reduction in VAS pain scores during delivery and with greater maternal satisfaction with the pain relief method and with the childbirth process.